(untitled) (Global Journal of Human-Social Science, 2024)
The article aims to investigate how the planning of teaching activities based on the historical movement of the process of emergence and development of mathematical concepts by a collective of Mathematics teachers in initial training contributed to the understanding that these concepts are a product of the humanitie needs and that the organization of Mathematics teaching in schools must address this understanding Related to this objective we sought to answer the following question What contributions can a training space called the Mathematics Club bring to the initial training of Mathematics teachers In the search for answers to this problem and to achieve the objective the formative experiment was chosen as research methodology happening from 2020 to 2023 The data analysis structure chosen was unit episodes and flashes The results shows that teachers were able to establish a historical understanding of the concepts that were approached